Reforestation and smallholder livelihoods in the humid tropics. (March 2020) - Ota, Liz; Herbohn, John; Gregorio, Nestor; Harrison, Steve
Highlights: We synthesised evidence from 339 papers on smallholder reforestation and livelihood. Reforestation can alleviate poverty with benefits beyond cash and subsistence goods. Reforestation is only one of smallholder livelihood portfolio activities Often reforestation benefits are not realized. Lack of availability and access to resources can limit reforestation outcomes. Abstract: Smallholder livelihoods and the restoration of tropical forests are intimately intertwined. To address the question of how reforestation affects livelihoods and how they in turn affect reforestation, a meta-synthesis was undertaken of 339 scientific publications identified from a systematic literature search. This study is focused on smallholders in the humid tropics, and uses the Sustainable Livelihoods Framework, which was developed by the UK Department for International Development as the framework for analysis. The links between reforestation and livelihoods are found to be diverse and highly interconnected. Reforestation is only one of a smallholder's activities and typically forms part of a mosaic of land uses across a landscape. Therefore, reforestation should be designed, managed and evaluated under the perspective of a diverse livelihood portfolio, and not as a single activity isolated from other portfolio components, especially under current landscape approaches. It is important for reforestation to be a complementary rather than a competitive livelihood activity. Reforestation has great potential to address poverty, and to increase smallholder socio-ecological resilience and local social equity. However, reforestation outcomes are often suboptimal. Assessing smallholder capacity and the surrounding environment prior to reforestation, and addressing limiting local capacities and conditions in a timely manner, may enhance the likelihood of optimal benefits.